2021
DOI: 10.1063/5.0067452
|View full text |Cite
|
Sign up to set email alerts
|

Use of an accelerated testing method to characterize inner front pole cover erosion in a high power Hall thruster

Abstract: Erosion characteristics on the cover of the inner front pole in a 12.5 kW Hall thruster were measured over a wide range of operating conditions in tests of 6–14 h duration using an accelerated test method and a very sensitive, radioactive tracer-based erosion diagnostic. The operating points included the nominal 300–600 V conditions on a constant 20.8 A throttle curve and conditions at other currents spanning the throttling envelope and with varying magnetic field strength, facility pressure, and discharge vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For example, a life test of * Author to whom any correspondence should be addressed. the 12.5 kW HERMeS thruster [2] showed that the maximum erosion rate of the inner pole cover reached 0.1 mm kh −1 at a 300 V discharge voltage and 0.04 mm kh −1 at a 600 V discharge voltage. The wear test results of a sub-kilowatt thruster showed that the overall average erosion rate of the magnetic pole was 0.01-0.084 mm kh −1 , however, the erosion rate at the maximum erosion position reached 0.496-0.849 mm kh −1 [3].…”
Section: Introductionmentioning
confidence: 98%
“…For example, a life test of * Author to whom any correspondence should be addressed. the 12.5 kW HERMeS thruster [2] showed that the maximum erosion rate of the inner pole cover reached 0.1 mm kh −1 at a 300 V discharge voltage and 0.04 mm kh −1 at a 600 V discharge voltage. The wear test results of a sub-kilowatt thruster showed that the overall average erosion rate of the magnetic pole was 0.01-0.084 mm kh −1 , however, the erosion rate at the maximum erosion position reached 0.496-0.849 mm kh −1 [3].…”
Section: Introductionmentioning
confidence: 98%